2015
DOI: 10.4081/mrm.2015.285
|View full text |Cite
|
Sign up to set email alerts
|

Medical malpractice, defensive medicine and role of the “media” in Italy

Abstract: Background: For many years until now, Italy has been subjected to an inconsistent and contradictory media campaign. On one hand the “media” present us with bold and reassuring messages about the progress of medical science; on the other hand they are prone to kneejerk criticism every time medical treatment does not have the desired effect, routinely describing such cases as glaring examples of “malasanità”, an Italian word of recent coinage used to denote medical malpractice. Newspaper reports of legal proceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
6
0
3
Order By: Relevance
“…According to the physician-related antecedent obtained as a result of this qualitative research, it was concluded that the most important antecedent was the fear of malpractice cases. This antecedent was the most mentioned in the literature due to its effect on defensive medicine (Catino, 2011; Toraldo et al, 2015). Another antecedent similar to the fear of being sued is the fear of being complained about and the patient’s complaint being made through a phone call.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the physician-related antecedent obtained as a result of this qualitative research, it was concluded that the most important antecedent was the fear of malpractice cases. This antecedent was the most mentioned in the literature due to its effect on defensive medicine (Catino, 2011; Toraldo et al, 2015). Another antecedent similar to the fear of being sued is the fear of being complained about and the patient’s complaint being made through a phone call.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, physicians perform medically unapproved practices to reduce the likelihood of malpractice (Project, 1971). Accordingly, defensive medicine occurs when physicians create diagnostic and treatment strategies that are not according to scientific evidence to avoid possible risky cases (Toraldo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Medical malpractice is a contentious topic in clinical care because it attracts a great deal of unfavorable attention from the public and patients, especially if a physician or hospital is found to be the recipient of a disproportionate number of medical malpractice litigations. Consequently, many litigations are resolved quickly and confidentially to minimize media exposure 15,16 . While this may protect the public image of a healthcare provider or institution, it prevents other physicians and clinicians from accessing the details of the litigation, which could potentially be used to improve clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A climate of clinical collaboration would be conducive to the best use of healthcare services [12], eventually reducing DM costs [20]. Moreover, it should be recognised that medicine is not an exact science [21,22] as certainty is non-existent in medical practice [23]. Patients' trust in physicians has decreased in the last decades, maybe because physicians' time spent with the individual patient has been reduced [24].…”
Section: Perspectivesmentioning
confidence: 99%